Ca8MgY(PO4)7:Eu2+,Mn2+ for better angular chromatic harmony and high lumen for white diode - Phuc Dang Huu; Phung Ton That; Phan Xuan Le; Nguyen Le Thai (Institute of Advanced Engineering and Science, 2022)
The multifunctional phosphor Ca8MgY(PO4)7doping with Eu2+ and Mn2+ ions (CaMn) is utilized to stimulate the rate of light extraction and color harmony of the white light-emitting diode (WLED) package using remote phosphor design with two sheets of phosphor. The CaMn sheet helps to reduce the color variation and light scattering backward mainly caused by high concentration of yellow phosphor YAG:Ce3+ film. The experimental results show a gradual increase of luminous flux and significant reduction of chromatic deviation in direct proportion to the increasing concentration of CaMn phosphor. Meanwhile, with more than 9% wt of CaMn concentration, the reduction of color rendering properties is presented because of the redundant green emission, leading to the lack of blue and yellow emission energies. Good color quality scale that peaks at 63 can be achieved with 2-4%wt. CaMn in the WLED packages. It is advisable to manage the concentration the green phosphor CaMn to attain desirable optical objectives.